Post-Harvest Management Practices Of Bambara Groundnut (Vigna Subterranea (L.) Verdc) Seeds In Burkina Faso - Ouili Amidou; Ynoussa Maiga; Adjima Ouoba; Hervé Nankangre; Cheik Omar Tidiane Compaore; Mahamadi Nikiema; Mahama Ouedraogo; Aboubakar Sidiki Ouattara (European Scientific Journal, ESJ, 2022)
Bambara groundnut plays a major role in the production systems and diets of farmers in Burkina Faso. This crop, due to certain production, storage, or preservation conditions, is subject to damage by insects and fungi. Effective post-harvest management can contribute significantly to reducing losses during storage. This study was carried out in the three agro-ecological areas in Burkina Faso to assess post-harvest management practices of Bambara groundnut among farmers. The data were collected from 180 farmers using surveys. The results showed that the culture of Bambara groundnut was mainly carried out by women (74.4%) on small farms (0.25-0.5ha). The harvested crops were dried at home during a period of 5 to 14 days. About 53% of farmers stored seeds for more than 3 months. Seeds were mainly stored in hermetically sealed cans (45.6%) and in plastic bags (31.1%). Some products such as wood ash and chemicals were used for seed storage. Challenges during seed storage were insects (91.4%) and fungi (42.9%). In the case of seeds attacked by pests (insects, fungi, etc.), farmers (84.4%) adopt a set of measures consisting of sorting, winnowing, drying, and repackaging the seeds. Besides the existence of traditional storage techniques, there is still a need to develop effective storage techniques and continue building farmers’ awareness on improved storage technologies to avoid post-harvest losses.